ESSENTIAL CHALLENGES IN IMPROVING EDUCATION QUALITY OF STUDENT LEARNING - ahmad (Yayasan Al-Afif, 2024)
Education is a fundamental pillar for building an advanced society. However, the education system faces numerous issues that hinder progress in learning quality. This article discusses essential challenges in the modern education world, with a particular emphasis on the efforts required to improve learning quality. The first challenge is access inequality, where the gap between urban and rural areas, as well as disparities in access, is a major obstacle in ensuring equitable education for all. Additionally, issues related to technology integration are also critical. For example, how technology can be used as a supportive learning tool without leaving behind students who cannot access it. The article also highlights job readiness, where the gap between the skills taught in schools and those required in the job market is a major issue. In efforts to improve education quality, several key areas need attention: the lack of social skills education, poor mental health education, an unsuitable curriculum, and educational inequality. To address these challenges, the article presents practical ideas and actions that can be taken by stakeholders in the fields of policy, teaching, and social intervention. By gaining a deep understanding of these issues, it is hoped that the education community can take concrete actions to improve education quality and create a more inclusive, adaptive, and responsive education system for future needs